The Relationship Between Learning Independence And Learning Motivation With IPS Learning Outcomes - Sidik Sulaksana; Ajat Sudrajat; Arifin Maksum (Buana Pendidikan, 2023)
This study aimed to determine the relationship between learning independence and learning motivation with social studies learning outcomes. This study uses an experimental method with an associative quantitative approach, which explains the presence or absence of influence between various variables based on the size of the correlation coefficient. This research was conducted on fifth-grade students in the first semester of SD Gugus V Ciracas District East Jakarta in the 2022/2023 school year with 100 samples. Data were collected through social studies learning outcomes tests. The analysis showed that the level of learning independence and motivation together had a strong and positive correlation with the learning achievement of Class V students in Gugus V, Ciracas District, East Jakarta. In other words, the higher the level of children's independence, the higher the learning outcomes. Likewise, learning motivation, in turn, improves learning outcomes.